2001
DOI: 10.1093/humrep/16.3.435
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric analysis of peri-implantation endometrium in patients having excessively high oestradiol concentrations after ovarian stimulation

Abstract: The present study investigated whether high oestradiol concentrations after ovarian stimulation in infertile women affect endometrial development around the time of implantation. The glandular and stromal components of the endometrium were assessed by morphometric criteria. Endometrial biopsies were taken on day 7 (+/-1) after the ovulating dose of human chorionic gonadotrophin in stimulation cycles and on day 7 after the LH surge in natural cycles. Women (n = 38) undergoing assisted reproduction treatment wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
57
0
3

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 132 publications
(66 citation statements)
references
References 20 publications
6
57
0
3
Order By: Relevance
“…Some reports claim a lack of benefit with higher oocytes number probably due to the detrimental effect of elevated steroid levels on oocytes quality, embryos aneuploidy and endometrial receptivity [5,30,31]. The biological advantages of natural cycle include the presence of a single oocyte of potentially better quality allowing the transfer of a healthier embryo into a more receptive endometrial environment [32].…”
Section: Discussionmentioning
confidence: 99%
“…Some reports claim a lack of benefit with higher oocytes number probably due to the detrimental effect of elevated steroid levels on oocytes quality, embryos aneuploidy and endometrial receptivity [5,30,31]. The biological advantages of natural cycle include the presence of a single oocyte of potentially better quality allowing the transfer of a healthier embryo into a more receptive endometrial environment [32].…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that exaggerated levels of E 2 have a negative impact on only oocyte quality (7,28,29). Moreover, elevated E 2 levels have been shown to convert endometrium into a hostile environment for embryo implantation (30), with a histological appearance of prematurely advancing endometrium (31). Conceivably, both endometrial and oocyte factors may contribute to an increased rate of early pregnancy loss.…”
Section: Discussionmentioning
confidence: 99%
“…We have examined the effects of excessive ovarian response on peri-implantation endometrial development using morphometric analysis of the glandular and stromal components of an endometrial biopsy taken on day 7 after the ovulating dose of hCG injection in stimulated cycles and on day 7 after the LH surge in natural cycles [38]. Excessive ovarian responders, i.e.…”
Section: Peri-implantation Endometrial Development By Morphometrymentioning
confidence: 99%